Assessing unprofessional behaviors of dental students through multi-source feedback: A mixed methods analysis of engagement and influencing factors - Maryam Kazemipoor; Shima Habibzadeh; Fatemeh Keshmiri (PLoS ONE, 2026)
Background Unprofessional behaviors have been identified as a hindrance to the professional identity formation of dental students. This study aimed to investigate dental students’ engagement with unprofessional behavior in a clinical setting and to explore their experiences regarding the factors influencing this behavior in dental school. Methods The sequential mixed-methods study conducted at Shahid Sadoughi University of Medical Sciences. A total of 140 dental students participated, selected through a census method. The quantitative phase focused on evaluating unprofessional behaviors among students using Multi-Source Feedback (MSF), which included assessments from clinical teachers, nurses, and self-evaluations by the students. In the qualitative phase, participants were chosen through purposeful sampling, and their experiences were explored through semi-structured interviews. Results Responses from all three groups of clinical teachers, nurses, and students showed that the highest students’ engagement with unprofessional behaviors was related to aspects of responsibility and respect. The highest engagement of unprofessional behavior was reported among junior learners (P = 0.0001) and male students (P = 0.0001). The students’ experiences were classified into a theme “disturbance of individual and systemic factors in the development of professional behaviors,” with two categories of “individualism” and “challenges of the overt and covert curriculum in professional development”. Conclusion The disruption of both individual and systemic factors has led to unprofessional behaviors at the dental school. On an individual level, issues such as a focus on profit and a reluctance to meet professional responsibilities have hindered adherence to principles of professionalism. At the systemic level, negative role models and inadequate educational requirements and training processes have also contributed to the prevalence of unprofessional behaviors among participants. Given generalizability limited to culturally similar educational contexts, other institutions may adopt MSF and targeted interventions on clinical role models and early responsibility training.